2021
DOI: 10.1242/bio.052332
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in the splicing regulator Prp31 lead to retinal degeneration in Drosophila

Abstract: Retinitis pigmentosa (RP) is a clinically heterogeneous disease affecting 1.6 million people worldwide. The second-largest group of genes causing autosomal dominant RP in human encodes regulators of the splicing machinery. Yet, how defects in splicing factor genes are linked to the aetiology of the disease remains largely elusive. To explore possible mechanisms underlying retinal degeneration caused by mutations in regulators of the splicing machinery, we induced mutations in Drosophila Prp31, the orthologue o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 81 publications
0
17
0
Order By: Relevance
“…In all experiments, young flies (2-4 days) were used. We used w ndelT , a null allele previously designated as w* in (Hebbar, Lehmann et al, 2021). In contrast to wild-type eyes, or to eyes mutant for w ndelT exposed for the same time to less stringent light conditions, e.g.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In all experiments, young flies (2-4 days) were used. We used w ndelT , a null allele previously designated as w* in (Hebbar, Lehmann et al, 2021). In contrast to wild-type eyes, or to eyes mutant for w ndelT exposed for the same time to less stringent light conditions, e.g.…”
Section: Resultsmentioning
confidence: 99%
“…Fig. S1A,B), or under light/dark conditions (Hebbar et al, 2021). Flies homozygous mutant for w and st (w;; st/st) have white eyes similar as w due to the absence of all screening pigments.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Vesicular Rh1 signals reportedly appear in flies exposed to light, becoming even more prominent in mutants that have defects in Rh1 trafficking to the lysosome (24,25). We found that vesicular Rh1 patterns in fabp EY06747 -/-eyes were also light-dependent, as extra-rhabdomeric anti-Rh1 signals mostly disappeared in flies raised under constant darkness (Fig 6E).…”
Section: Rh1 Protein Localization In Fabp Mutantsmentioning
confidence: 60%
“…Rh1 forms a stable complex with Arrestin and together undergo endocytosis [18][19][20][21]. The photoreceptors need to degrade those endocytosed Rh1, as excessive Rh1 accumulation in the endosome/lysosome can cause lightdependent retinal degeneration [18,19,[22][23][24][25][26]. These aspects appear to be conserved across phyla, as the human Rhodopsin mutants that exhibit high affinities for Arrestin display endosomal abnormalities and are associated with severe forms of ADRP [27,28].…”
Section: Introductionmentioning
confidence: 99%